Type 2 diabetes with obesity and hypertension: prevalence and sociodemographic risk factors in Yemen - S. S. Mareai; K. Gawli (Сахарный диабет)
BACKGROUND: Diabetes Mellitus is a rapidly growing and challenging health issue of the 21st century. Type 2 diabetes (T2D) is a major risk factor for obesity and hypertension (HTN). The prevalence of HTN and obesity in T2D patients is not well documented in the country of Yemen. AIM: The focus of this study was to assess the prevalence of hypertension and obesity in patients with type 2 diabetes mellitus in Yemen.METHODS: A cross-sectional study was carried out in Dhamar city hospitals. Patients diagnosed with diabetes (300 males and females: 30 years old and/or above) visiting an endocrinology and diabetes clinic in Dhamar city hospital for the first time were examined and evaluated for blood glucose levels, mode of treatment, duration of the disorder and body mass index. Socio-demographic and clinical data were collected using pretested questionnaires. Ethical approval was obtained from corresponding ethical committees from Dhamar University and hospitals. Data were analyzed using SPSS 23 version.RESULTS: The prevalence of overweight and/or obesity in T2D was 60.67%, and hypertension was 35.66%. The occurrence of T2D was predominant in females (56.33%), patients with an age over 50 years (61%), and rural dwellers (74%). The mode of treatment was mainly through oral antihyperglycemic and hypoglycemic agents (79.3%). A large population (66.3%) showed poor control of blood glucose levels ranging from more than 131 to 500 mg/dL and the type of work these patients were involved in was mostly physically inactive (64%). The body mass index revealed that more than 35% were found to be overweight and 23% to be obese. Patients with hypertension and undergoing treatment for the same showed a significant (P < 0.001) increase in blood glucose level compared to those who were not diagnosed with HTN.CONCLUSION: The prevalence of obesity, HTN, and poor glycemic control in patients with T2D is high, especially in females.